A snake's coils are even more intricate than a mole's burrow.: Individualization and subjectification in post-disciplinary regimes of work - Richard Weiskopf; Bernadette Loacker (Management Revue, 2006)
In contemporary discourse it is almost commonplace to describe societies and work relations as highly individualized. In this article we develop a conceptual framework that enables us to discuss processes and practices of individualization as political technologies. Following a line of thinking influenced by Michel Foucault and Gilles Deleuze, we first illustrate three different regimes of work. The main focus is on elaborating and illustrating characteristics of the post-disciplinary regime of work which allows us to systematize fundamental shifts in the way of organizing and managing work. We then analyze contemporary strategies for producing the 'appropriate individual' as 'technologies of modulation' that focus on the production of the autonomous, flexible and adaptable subject. We suggest that these strategies are highly ambivalent and must not be seen in a deterministic way. They are necessarily an interplay of technologies that determine the conduct of individuals and 'technologies of the self'. This is reflected in the process of subjectification that contains both possibilities for increased subjection and for self-creation.
Keywords: 650; governmentality; individualization; post-disciplinarity; regimes of work; subjectification; technologies of the self